The evolution of peripheral nerve treatment for trigeminal neuralgia - peripheral nerve surgery - Ngeow, WC; Choon, YF; Chai, WL; Tan, CC; Lim, Daniel (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Trigeminal neuralgia typically presents with a sudden and severe facial pain. Although peripheral nerve injection can produce good pain relief in the treatment of trigeminal neuralgia, their effect may not be permanent. Surgical treatment has always been an alternative for patients who do not respond well to medical treatment or, for those who are severely affected by the side effects of anticonvulsants. Unknown to most young healthcare providers, surgical treatment was the first line treatment at the turn of the 19th century till 1960s. This review narrates the evolution of peripheral nerve treatment for trigeminal neuralgia over the last 150 years.